If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2x + -9 = 35 Reorder the terms: -9 + 2x = 35 Solving -9 + 2x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2x = 35 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 35 + 9 2x = 35 + 9 Combine like terms: 35 + 9 = 44 2x = 44 Divide each side by '2'. x = 22 Simplifying x = 22

| 9+(8-15)=x+64 | | 74-4x=23x+17 | | 3z+6=-84-7x | | 4j+3=-13 | | 169-4x=6x+19 | | 34x+25=18 | | x^2+23x+60= | | 3(2n+4)=2(3n-6) | | 165-6x=21x+18 | | 11x+30=6x+130 | | 9+(8-15)=x+48 | | 156-7x=29x+20 | | 9n-n^2-220=0 | | 6+(8-15)=x+12 | | 5-10x=53-24x | | 67-7x=11x+17 | | -4(w-1)=7w-40 | | 9n-n^2-220= | | 3x+1=-14 | | (X^2+5x)-104=0 | | 5-10x=53-38x | | 5x+6x*34x-x+18=88 | | 4x+10+2x=52 | | 3(y+5)-6y=24 | | 4x+8(8)=-16 | | 9+7x+2x=18 | | 164-7x=29+24 | | 3(9-14)=y-9 | | 6/2*(1+2)=x | | 13-7x=54-14x | | 3x+29=12x-43 | | 2(9-10)=y-5 | | 4a-4a=4+28 | | 6/3*(2+1)=x | | 3x+13=-95-9x | | -42+8+y=-6+10 | | 2x+6+6x=62 | | -28-6x=8-10x | | -21+5+y=-9+13 | | 5(2y-3)=24-3y | | 9(4)-8y=42 | | 4a-4a= | | 28-2.4y=11.6y+266 | | -(5y+3)-(-4y-5)=1 | | 9y-8y+4=-9 | | 3+4x=39 | | 6x*2(2+1)= | | 12-8x=122-43x | | 6x-5x-3=5 | | 4x^2+4x-174=0 | | 2x+3(8)=28 | | 4(30-y)+3y=100 | | -7(x-3)=4 | | 8b+4+6b=-3b+9 | | 9=n-38 | | 1(2)=8y | | 5x-19=3x-15 | | 36z-86=-2z+28 | | 11x+29=4x+232 | | x-1(3)=4 | | w+92=6w+82 | | 6(3x-7)=3(6x+2) | | 23x-4=34x | | -10x^2=-270 | | 3x^2-6x-4=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics